Dense sampling provides a reevaluation of the southern geographic distribution of the cavies Galea and Microcavia (Rodentia) - Udrizar Sauthier, Daniel Edgardo (2015)
The southern distribution of the small cavies Galea leucoblephara and Microcavia australis is reviewed. It has been enriched through the addition of 36 new locality records for G. leucoblephara and 176 for M. australis. Both caviomorph rodents are widespread in Patagonia – the former occurs in the northern portion of the territory, whereas the latter is recorded up to the Strait of Magellan. The reference of Patagonian Galea populations to leucoblephara is still subject to confirmation. Therefore, the status of negrensis must be addressed in future studies. For southern Microcavia australis populations, a rich subspecifical scenario is proposed, including the names australis, kingii, and nigriana. The alpha taxonomy of this cavy needs a fresh approach that is based on a larger sample set coupled with the analysis of molecular markers.